(untitled) (The New Uzbekistan Journal of Medicine, 2025)
Desloratadine is an effective histamine H1 receptor blocker in the complex treatment of patients with various allergic diseases. The article presents literature data on the clinical efficacy and safety of desloratadine in the treatment of autoimmune urticaria of various etiologies and courses.